Cumulative Live Birth Rates in Low Prognosis Patients According to the POSEIDON Criteria: An Analysis of 26,697 Cycles of in vitro Fertilization/Intracytoplasmic Sperm Injection - Li, Yuan; Li, Xiaofeng; Yang, Xiaoyi; Cai, Sufen; Lu, Guangxiu; Lin, Ge; Humaidan, Peter; Gong, Fei (Frontiers in Endocrinology, 2019)
Objective: The POSEIDON stratification is used to stratify patients with low prognosis after assisted reproductive technology (ART) treatment. There is no published clinical study using the POSEIDON stratification in China. We used the POSEIDON stratification in Chinese women receiving repeated ART treatment and analyzed the association between this stratification and the cumulative live-birth rate (CLBR). Methods: This was a retrospective cohort study of 62,749 women (97,388 cycles) who received ART treatment at the Reproductive and Genetic Hospital of CITIC-XIANGYA between January 2014 and June 2017. A total of 19,781 (31.52%) women who fulfilled the POSEIDON criteria were stratified, resulting in a total of 26,697 cycles. The optimal and conservative CLBRs within a complete IVF/ICSI treatment cycle and CLBRs following repeated ovarian stimulation cycles were calculated. Results: In the POSEIDON groups 1, 2, 3, and 4, the optimal and conservative CLBRs of three complete consecutive in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment cycles were 83.87% and 66.06%, 53.67% and 37.72%, 44.24% and 27.98%, and 14.20% and 9.68%, respectively. The POSEIDON stratification was associated with live birth in the first stimulation cycle (group 2: odds ratio [OR]=2.310, 95% confidence interval [CI]: 2.121-2.515, P<0.001; group 3: OR=1.359, 95% CI: 1.008-1.833, P=0.044; group 4: OR=3.505, 95% CI: 2.758-4.454, P<0.001; all vs. group 1). For the second stimulation cycle, the POSEIDON stratification was still associated with live birth, except in POSEIDON group 3 (group 2: OR=2.096, 95% CI: 1.76-2.495, P<0.001; group 4: OR=3.863, 95% CI: 2.709-5.507, P<0.001). A change in ovarian stimulation protocol was not associated with an improvement in live birth. Conclusions: More than 30% of women receiving IVF/ICSI treatment may be classified as low prognosis patients. Different reproductive outcomes were observed among the four POSEIDON groups. The most optimal outcomes after three successive cycles of IVF/ICSI treatment were noted in groups 1, 2 and 3.